How to be psychologistic about motivating but not about normative reasons - Mantel, Susanne (Grazer philosophische Studien, 2016)
Because normative reasons are non-psychological, and motivate us when we act for them, some have concluded that motivating reasons have to be non-psychological, too. This thought has served as part of an argument against the Causal-Psychological Account of Action, because the account states that motivating reasons are psychological. Recently, many authors recognized that there are two different notions of motivating reasons which are commonly being confused in this dispute. While the Anti-Psychologist is right that motivating reasons in her sense need to be classified as non-psychological, the proponent of the Causal-Psychological Account refers to something else by the term ‘motivating reason’ and rightly claims that it is psychological. However, this insight has not gained the uptake it deserves, partly because it has not been presented by way of a systematic evaluation of the different readings of the argument against the Causal-Psychological Account. This paper’s aim is to point out more carefully the argument against the Causal-Psychological Account and the dilemma faced by that argument. This will hopefully show that and why motivating reasons - in the sense in which they figure in the Causal-Psychological Account - can be psychological even if agents act for non-psychological normative reasons.
Gesehen am 23.12.2025